Development of Canva-Based Islamic Religious Education Teaching Materials to Support Independent Learning for PPG Students at the State Islamic University - Fauziah Nasution; Suparni Suparni; Farhani Azkia (AL-ISHLAH: Jurnal Pendidikan, 2025)
The implementation of the independent learning paradigm within the Teacher Professional Education (PPG) program requires teaching materials that are flexible, engaging, and aligned with professional competency demands. In Islamic Religious Education (PAI), existing materials often lack visual support, contextual relevance, and higher-order thinking integration, which may limit students’ independent learning readiness. This study aimed to develop and evaluate Canva-based PAI teaching materials grounded in the independent learning paradigm for PPG students at a State Islamic University. A Research and Development (RD) approach based on the Borg and Gall model was employed, focusing on product validity, practicality, and effectiveness. Product validity was assessed by three expert validators consisting of subject-matter, language, and media experts. Practicality was evaluated through questionnaires completed by lecturers and supervising teachers. Effectiveness testing involved 120 in-service PPG Batch 1 students at UIN SYAHADA Padangsidimpuan in 2024. Data were collected through questionnaires, observations, and learning outcome tests. The developed teaching materials, designed as Canva-based PowerPoint slides integrated with a Higher Order Thinking Skills (HOTS) question bank aligned with the Knowledge Test blueprint, demonstrated strong evaluation results. The average validity score was 4.26 out of 5, indicating high validity. Practicality achieved an average score of 4.37, categorized as very practical, while effectiveness reached an average score of 4.60, categorized as very effective. Additionally, the graduation rate increased from 84.5% prior to implementation to 99.9% after use of the materials. These findings indicate that the developed Canva-based PAI teaching materials are valid, practical, and supportive of independent learning in the PPG context, offering a promising instructional resource for Islamic teacher education.